SOCIAL CAPITAL SOCIETY OF FISHERMEN VILLAGE OF PAMBANG PESISIR BANTAN SUB-DISTRICT BENGKALIS REGENCY RIAU PROVINCE - Giska Regina; Zulkarnain Zulkarnain; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The reseach to know social capital structure in the fishing community,to know the function of social capital in fishing communities, to find out the most dominant forms of social capital in fishing comumnities. This reseach was conducted in march 2019. Selection of reseach locations done intentionally, with consideration that pambang pesisir village themajority of residents make a living as fiherman.The method used in this study is a case study which examines the satus of subject of reasaech relating to a typical phase of overall personality. Informants in this study include there types, namely : (1)key informan, (2) ordinary informant, (3) additional informant. This research shows that structure of social capital in fishing communities can be seen from participation in networks, reciprocal relationship, trust, social norms, values, and proactive actions. The function of social capital in fishing communities is known as problem solving, community unfication tool, and build community participation. The form of social capital of fishing communities is bound social capital tends to be exclusive, what are the basic charateristics inherent in typology, social capital bridges the modern form of grouping, associstion group or community, social capital network that conncts and reashes different people in different situations. Keywords : Social Capital, Fishing Community, Pambang Pesisir